The Influence of Organizational Communication on Employee Performance Mediated by Employee Job Satisfaction at the Denpasar City Health Office - Anak Agung Gde Wimanta Wari Bawantu; I Gusti Made Suwandana (International Journal of Economics and Management Sciences, 2024)
This research took the location, namely the Denpasar City Health Service. Within the company there are 5 fields available to support integrated health service programs for the community, with a total human resource population of 61 emoployee. The health development program has been implemented with reference running into half decade Strategic Planning which is outlined in the annual performance plan. The health development was carried out in the form of 18 existing health development programs. The pre-survey results showed the influence of employee performance variables using seven questions. 14 samples said they did not agree to the seventh question, 5 respondents answered by choosing the word "disagree" to the sixth question. , namely "work equipment and facilities are adequate and support me in my work", there is a research gap that took place in I News Jakarta stating the results show that communication variables have no effect on employee performance. The aim of this research was to find out how organizational communication influences employee performance, find out the effect of communication on job satisfaction, find out the effect of job satisfaction on employee performance, and find out the role of job satisfaction in mediating organizational communication on employee performance. The research methods used include the interview process and questionnaires. This research measurement used saturated sampling a sample sized are 61 employee was used. The research results found that the organizational communication variable had a significantly positive effect on employee performance, organizational communication had a significantly positive effect on job satisfaction, organizational communication had a significantly positive effect on job satisfaction and the influence of job satisfaction significantly positively mediated organizational communication affect performance employee.